Mental Health as a Global Development Challenge: A Critical Analysis of the Case in Nepal - Buerkner, Jonas F.; Walsh, Christine A. (Molung Educational Frontier, 2023)
This paper builds on primary literature to provide a critical analysis investigating mental health as a global development challenge in the context of Nepal. First, the Nepalese mental healthcare context is introduced and reviewed. Second, challenges for mental healthcare progress in Nepal are examined, and solutions are suggested. Third, this analysis considers the critical role of Nepalese traditional healers in the solution to its mental healthcare challenge. Further, community development is discussed in the context of mental healthcare, and finally, suggestions are devised for global mental health promotion.